Deep venous thrombosis in a patient with therapeutic INR for PS deficiency - Vamegh, Motahareh; Hallak, Ahmad; Abousherif, Wael (International Journal of Research in Medical Sciences, 2017)
We have reported a rare case of DVT in a 25-year-old patient with a known case of Protein S deficiency with INR within therapeutic index. He was seen in the ED and transferred to the Medical ward after diagnosis in the ED using doppler US. The patient was successfully treated with heparin and warfarin with a higher than usual optimal INR. This case adds to the growing evidence that PS deficiency is one of the rare causes of DVT, and also raises awareness that thrombosis can still occur in the current optimal INR for such patients. This case report necessitates the revision of what should be the optimal INR for patients with Protein S deficiency who develop thrombosis in the current optimal INR.